Guyana : the struggle for liberation (1945-1992) - Sallahuddin (The author GeorgetownGY, 1994)
Focuses on the political struggle in British Guiana from 1945 to 1966 and the critical role played by Dr. Jagan. Looks at the formation of the People's Progressive Party, its first essay into government and its continuing role. Highlights special subjects and matters in the period 1960-92 such as the elections, referendum and the Burnham and Hoyte regimes.